Biocompost and Arbuscular Mycorrhizal Fungi on Chemical Properties of Inceptisols and Root Infection in Purple Corn Plants - Yusra, .; ., Rosnina; Aryani, Dewi Sartika (JOURNAL OF TROPICAL SOILS, 2021)
The purpose of this study was to evaluate the application of biocompost and mycorrhizae fungi on chemical properties of inceptisol soil and root infection on purple corn plants. This research was conducted in October-December 2020 at Experimental Garden, Faculty of Agriculture, Universitas Malikussaleh in Reuleut Village, Muara Batu District, Aceh Utara, employing Randomized Block Design (RBD) Factorial with 2 factors observed. The first factor observed was different doses of biocompost: B0 (0 ton/ha, 0 g/plot), B1 (5 tons/ha, 1500 g/plot), B2 (10 tons/ha, 3000 gr/plot) and B3 (15 tons/ha, 4500 gr/plot). The second factor was M0 (0 ton/ha, 0 gr/plot, 0 g/plant), M1 (0.25 tons/ha, 75 g/plot, 5 g/plant) dan M2 (0,5 ton/ha, 150 g/plot, 10 g/plant). The results indicated that the application of biocompost together with mycorrhizae has increased soil pH from 5.0 to 5.5 and the application of biocompost alone has improved the organic C (1.58% to 2.98%) and the application of mycorrhizae improved the root infection by 90%. The application of 5 ton/ha biocompost and 0.5 ton/ha mycorrhizae were to be found to be the best doses to improve the chemical properties of inceptisol soil and mycorrhizal infection.Keywords: biocompost, inceptisols, purple corn, mycorrhizal fungi